2020
DOI: 10.5755/j01.itc.49.1.23801
|View full text |Cite
|
Sign up to set email alerts
|

Shadow IT – Systematic Literature Review

Abstract: Shadow IT coexists with mandated information systems. Developed and applied by non­IT domain experts, it is as a rule, but not exclusively, used for resolving non­routine issues, for which mandated IS does not have appropriate functions. Shadow IT solutions are not supported or controlled by IT departments. The aim of the paper is to show to which extent shadow IT has been researched, as this area has not yet received the necessary attention from both academia and business. A systematic literature review was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Existing literature [42] indicates that governing shadow IT or, more generally, the usage of personal IT space is unlikely to be beneficial for both organizations and users without some sort of dialogue. One survey [43] of three private and two public companies has also identified how hard it is to come to an agreement between an organization and its employees when users are very selective in what policy and regulation details they are willing to accept.…”
Section: Personal Devices and Shadow It Byodmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing literature [42] indicates that governing shadow IT or, more generally, the usage of personal IT space is unlikely to be beneficial for both organizations and users without some sort of dialogue. One survey [43] of three private and two public companies has also identified how hard it is to come to an agreement between an organization and its employees when users are very selective in what policy and regulation details they are willing to accept.…”
Section: Personal Devices and Shadow It Byodmentioning
confidence: 99%
“…There are also a number of open research directions [42] that can be identified for future shadow IT research, e.g., exploring generation Z's attitudes and behaviors towards shadow IT.…”
Section: Personal Devices and Shadow It Byodmentioning
confidence: 99%
See 1 more Smart Citation
“…Association rules (AR) method involves constructing associative rules on the excessiveness of available data [20,22]. Firstly, all received rules are sorted by some parameter (for example, authenticity).…”
Section: Methods Of Imputation (Restoration Filling)mentioning
confidence: 99%
“…That might be nonexistent when it comes to investigating mobile shadow IT usage. Besides, Raković et al (2020) conducted a systematic literature review to show to which extent shadow IT has been researched. This area has not yet received the necessary attention from both academia and business.…”
Section: Literature Reviewmentioning
confidence: 99%